EXPLORING COLLOCATIONS IN BAHASA INGGRIS TEXTBOOK: A CORPUS STUDY - Raden Indrajid Lukman Sarjono; Ayuni Kabobu Heda; Barli Bram (Jurnal Penelitian Humaniora, 2022)
This paper explored the types of collocations used in an English textbook entitled Bahasa Inggris (SMA/MA/SMK/MAK, Kelas X, Semester 1). The primary source of data was the textbook, entitled Bahasa Inggris, which was published by the Indonesian government for the first-year or class 10 students of senior high schools (SMA/MA/SMK/MAK). This study was a corpus analysis. The researchers utilized AntCont 3.5.8 to extract and discover the required data and then explored the types of collocations used in the Bahasa Inggris textbook. The results showed that the textbook comprised of Grammatical G1 (1807), Grammatical G3 (178), Grammatical G4 (1770), Grammatical G5 (1), Lexical L1 (594), Lexical L3 (125), Lexical L5 (21), and Lexical L6 (1). Grammatical G1 collocation was the most frequent type in the textbook. The results indicated that it would be beneficial for English teachers to provide collocation materials for the students to accommodate their writing and speaking skills.